2022
DOI: 10.3390/biomedicines10020514
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide and Its Soluble Analogues: Multitasking Compounds with Antitumor Properties

Abstract: Due to its chemical properties and multiple molecular effects on different tumor cell types, the sesquiterpene lactone parthenolide (PN) can be considered an effective drug with significant potential in cancer therapy. PN has been shown to induce either classic apoptosis or alternative caspase-independent forms of cell death in many tumor models. The therapeutical potential of PN has been increased by chemical design and synthesis of more soluble analogues including dimethylaminoparthenolide (DMAPT). This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 196 publications
(254 reference statements)
0
17
0
Order By: Relevance
“…As a result, those metabolites were mainly involved in the lipid metabolism, tricarboxylic acid cycle, choline metabolism, and amino acid metabolism. These results indicated that parthenolide could inhibit the development and proliferation of PTC cells by accelerating oxidative stress response and metabolic imbalance, especially in amino acid and lipid changes [5,12]. Then we demonstrated that parthenolide could lead to proteomic differences in PTC cells (BCPAP cells) [13].…”
Section: Introductionmentioning
confidence: 73%
“…As a result, those metabolites were mainly involved in the lipid metabolism, tricarboxylic acid cycle, choline metabolism, and amino acid metabolism. These results indicated that parthenolide could inhibit the development and proliferation of PTC cells by accelerating oxidative stress response and metabolic imbalance, especially in amino acid and lipid changes [5,12]. Then we demonstrated that parthenolide could lead to proteomic differences in PTC cells (BCPAP cells) [13].…”
Section: Introductionmentioning
confidence: 73%
“…In esophageal carcinoma, parthenolide (PTL) has been found to suppress the NF-кB/AP-1/VEGF signaling pathway [ 77 ]. Moreover, PTL has been revealed to induce classic apoptosis, as well as alterations in the Bcl-2 family and rising reactive oxygen species (ROS) production intracellularly [ 78 ]. PTL exerts proapoptotic stimulation of p53, together with reduced glutathione reduction [ 79 ].…”
Section: Chemoprevention Mechanisms Of Plant-derived Productsmentioning
confidence: 99%
“…PTL can induce apoptosis by the initiation of DNA hypomethylation, histone acetylation, enhancement of oxidative stress via endoplasmic reticulum or thiol depletion, and activation of p53. In addition, PTL has shown its ability to significantly inhibit cell growth and induce G0/G1 cell cycle arrest [ 310 ] via several mechanisms such as transcriptional regulation, signal transduction modulation, and induction of oxidative stress [ 78 ]. In prostate cancer cells, PTL induces cell cycle arrest via the inhibition of miR-375 [ 311 ].…”
Section: Plant-derived Natural Products With Potential Anticancer Eff...mentioning
confidence: 99%
“…To understand the pharmacological effects of PTL, in vitro studies on its efficacy, pharmacological activities, and potential molecular mechanisms in a variety of cancer cells as well as available in vivo models since 2019 are tabulated in Table 1 , thus further extending and qualifying existing reviews of its biological activities. 3 , 4 , 50 As shown in Table 1 , PTL modulation toward the aforementioned signaling pathways and cellular processes exerts multiple pharmacological effects against a myriad of tumor cell types.…”
Section: Antitumor Mechanisms Of Ptlmentioning
confidence: 99%
“… 33 , 72 Indeed, a large number of studies reported that PTL was capable of inducing autophagic or necrotic cell death. 50 , 62 For instance, PTL mediated cell death through ROS-mediated autophagy in human osteosarcoma (Saos-2 and MG-63) and triple-negative breast cancer (MDA-MB-231) cells. 40 , 43 In particular, PTL was capable of simultaneously inducing mixed forms of cell death, as evidenced by observations of PTL-induced apoptosis and autophagy in Hela and HepG2 cells as well as apoptosis and necrosis in HL60 cells.…”
Section: Antitumor Mechanisms Of Ptlmentioning
confidence: 99%